Evaluation of the implementation of school exams using the brinkerhoff model in physics subjects in senior high school - Rabiyanti B. Kamali; Masri Kudrat Umar; Dewi Diana Paramata; Supartin Supartin; Tirtawaty Abdjul; Dewa Gede Eka Setiawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
School exam is one of the benchmarks of student learning outcomes as a test that is expected to provide information on the ability of students that can be used to consider and describe the achievement of students, especially in physics subjects. This study aims to describe the suitability of fixed vs. emergent design, formative vs. summative design, experimental design, and quasi-experimental vs. natural inquiry evaluation of the implementation of school exams in physics subjects in high school. This research uses the Brinkerhoff evaluation model proposed by Robert O. Brinkerhoff. The method used in this research is quantitative, and this type of research is evaluative. The data collection technique used a questionnaire, supported by observation and documentation, and a literature study to give meaning to the research results. The results showed that overall the organization of school exams in physics subjects in high school was very good. In the fixed vs. emergent design component, a total average of 95% is obtained from the teacher's perspective and 87% from the student's perspective, which is very good. Furthermore, for the formative vs. summative design component, a total average of 94% was obtained from the teacher's perspective and 88% from the student's perspective, which was in the excellent category. Then the experimental design and quasi-experimental vs. natural inquiry obtained a total average of 96% in the teacher's perspective and 88% in the student's perspective, which is in the excellent category. Thus, the implementation of school exams in physics subjects in high school is very good, but further research needs to be carried out to analyze, maintain, and at the same time improve what is lacking in terms of organizing school exams, starting from the preparation, implementation, and closing stages.